Degradation of nickel from electroplating wastewater by using ultrasonic assisted extraction in addition of HCL - Mohd Firdaus, Sudeerman (2010)
Nickel is one of the heavy metals which are having a high relative atomic mass that can cause an environmental pollution and potential hazard to human health. The method currently practiced for the degradation of heavy metal is by using ultrasonic assisted extraction. Even in low concentration, heavy metal is considered as toxicity and imposes considerable risk on all forms because of their suspected carcinogenic properties. If hazardous compound spreading to environmental, high of energy is needed to treat it and leads to the high of cost operation. Other methods for degradation heavy metals take a longer extraction time. The degradation of nickel from electroplating wastewater was investigates by using 37 kHz ultrasonic cleaner and extraction assisted with solvent, HCl and without solvent. Experiments were carried out at concentration of solvent, HCl (1-3 mol/dm3), sonication time (2-30 minutes), temperature (40-80oC) and volume of solvent, HCl (1-15 mL). The comparison of nickel degradation with solvent and without solvent also has been studied. In presence of solvent, the percentage of nickel degradation was higher than without solvent. The higher percentage of nickel degradation was at 2.5 mol/dm3 of solvent concentration (70.0 % nickel degraded), 20 minutes of sonication time without solvent (69.1 % nickel degraded) and with solvent (77.5% nickel degraded), temperature was at 60C without solvent (67.7% nickel degraded) and with solvent (75.5% nickel degraded) and volume of solvent was at 2 mL (78.8% nickel degraded). Finally, the result of the study showed that the nickel degradation increased with increasing solvent concentration, sonication time and temperature of degradation and decreasing volume of solvent. The best condition for all parameter applied was degraded 77.8% of nickel.